Preparation of Waterborne Epoxy Resin for Carbon Fibers Sizing Agent - Chen, Juan; Ge, Heyi; Liu, Jianye; Zhou, Xinrui; Wang, Dongzhi (Asian Journal of Chemistry, 2012)
In this paper, according to the molecular design, a waterborne epoxy resin for carbon fiber sizing agent was synthesized with poly-functional group novolac epoxy resin (F-51) and diethanolamine by self-emulsifying method. The effects of reaction temperature and time on the structure of modified resin were investigated. Fourier transforms infrared spectrum was used to characterize the molecular structure of the modified resin. To investigate the conversion rate of epoxy group, the epoxy value (EV) of the modified and unmodified resin was measured by hydrochloric acid-actetone method. The water-solubility of the modified epoxy resin was also studied. The results showed that the optimum reaction temperature and time were 80 ºC and 2 h, respectively. The modified epoxy resin has good water-solubility and high storage stability, which was suitable as sizing agent for carbon fibers.